MiR-148a inhibits oral squamous cell carcinoma progression through ERK/MAPK pathway via targeting IGF-IR. Issue 4 (21st April 2020) - Jia, Tingting; Ren, Yipeng; Wang, Fengze; Zhao, Rui; Qiao, Bo; Xing, Lejun; Ou, Long; Guo, Bin
Abstract: Objective: The current study aimed to investigate the functional roles and clinical significance of microRNA-148a ( miR-148a ) in the progression of oral squamous cell carcinoma (OSCC). Methods: Relative expression of miR-148a in OSCC cells and tissues were detected using quantitative real-time polymerase chain reaction (qRT-PCR). Chi-square test was performed to estimate the relationship between miR-148a expression and clinical characteristics of OSCC patients. Cell transfection was carried out using Lipofectamine® 2000. Biological behaviors of tumor cells were detected using 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) and transwell assays. Bioinformatics analysis and luciferase reporter assay were used to identify the target genes of miR-148a . Protein expression was detected through Western blot analysis. Results: MiR-148a expression was obviously decreased in OSCC tissues and cells, and such down-regulation was closely correlated with lymph node metastasis ( P =0.027) and tumor node metastasis (TNM) stage ( P =0.001) of OSCC patients. miR-148a overexpression could significantly impair OSCC cell proliferation, migration and invasion in vitro ( P <0.05 for all). Insulin-like growth factor-I receptor (IGF-IR) was a potential target of miR-148a. MiR-148a could inhibit ERK/MAPK signaling pathway through targeting IGF-IR. Conclusion: MiR-148a plays an anti-tumor role in OSCC and inhibits OSCC progression through suppressing ERK/MAPK pathway via targeting IGF-IR.